Evolution and trend of landslide research in India based on a decade long publication record - Ashutosh Kainthola; Vishnu Himanshu Ratnam Pandey; Gaurav Kushwaha; Kumari Priya; P. K. Singh; T. N. Singh (Discover Geoscience)
Abstract This study analyses trends in landslide publication in India, between 2010 and 2020, focusing on 79 studies, sourced from platforms like Google Scholar, ResearchGate, Web of Science, and ScienceDirect. The analysis reveals that approximately 65% of the publications were featured in Q1 and Q2 journals, with significant contributions from premium institutions like IIT-B (Mumbai), IIT-ISM (Dhanbad), and WIGH (Dehradun). The studies primarily focus on regions such as Uttarakhand, Himachal Pradesh, Tamil Nadu, and Kerala. Remote sensing and GIS emerged as the most frequently used approaches, appearing in 31 studies, followed by empirical methods (25 studies) and numerical techniques (20 studies). Researchers duly examined susceptibility, vulnerability, and risk using statistical techniques, with kinematic analysis and Slope Mass Rating (SMR) being notable empirical methods. The finite-element method was preferred for numerical slope failure analysis. The study found that 57% of the publications relied on existing data without conducting laboratory tests, while the remaining 43% conducted tests focusing on rock strength, shear strength, and physico-mechanical parameters. Direct shear tests and unconfined compressive strength (UCS) were the most commonly performed laboratory tests. Lithological analysis identified 20 different rock/soil types, with gneiss, quartzite, sandstone, and others frequently documented. Mitigation strategies such as informed decision-making, mechanical remediation, drainage system installation, and slope re-scaling were commonly suggested. Among the 31 computer-based programs used, ArcGIS, DIPS, and RS2 were the top tools for assessing mass-movement issues. The most common failure types reported were rock falls, debris flows, and rock slides, with rainfall identified as the primary landslide-triggering factor in 52 instances. The study highlights geology, geomorphology, and hydrology as key aggravating factors for landslide instances.